Adrenergic Modulation of Erythropoiesis After Trauma - Munley, Jennifer A.; Kelly, Lauren S.; Mohr, Alicia M. (Frontiers in Physiology, 2022)
Severe traumatic injury results in a cascade of systemic changes which negatively affect normal erythropoiesis. Immediately after injury, acute blood loss leads to anemia, however, patients can remain anemic for as long as six months after injury. Research on the underlying mechanisms of such alterations of erythropoiesis after trauma has focused on the prolonged hypercatecholaminemia seen after trauma. Supraphysiologic elevation of catecholamines leads to an inhibitive effect on erythropoiesis. There is evidence to show that alleviation of the neuroendocrine stress response following trauma reduces these inhibitory effects. Both beta blockade and alpha-2 adrenergic receptor stimulation have demonstrated increased growth of hematopoietic progenitor cells as well as increased pro-erythropoietic cytokines after trauma. This review will describe prior research on the neuroendocrine stress response after trauma and its consequences on erythropoiesis, which offer insight into underlying mechanisms of prolonged anemia postinjury. We will then discuss the beneficial effects of adrenergic modulation to improve erythropoiesis following injury and propose future directions for the field.